1999
DOI: 10.1017/s0960129599002777
|View full text |Cite
|
Sign up to set email alerts
|

Hidden coinduction: behavioural correctness proofs for objects

Abstract: This paper unveils and motivates an ambitious programme of hidden algebraic research in software engineering. We begin with an outline of our general goals, continue with an overview of results, and conclude with a discussion of some future plans. The main contribution is powerful hidden coinduction techniques for proving behavioural correctness of concurrent systems, and several mechanical proofs are given using OBJ3. We also show how modularization, bisimulation, transition systems, concurrency and comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 39 publications
(57 reference statements)
1
23
0
Order By: Relevance
“…However, in most of the cases it is possible to consider only a finite set of contexts C Σ ⊆ C {s} Σ instead of the set C {s} Σ , inducing this way the formation of finite specifications SP s (cf. [1,12,19]). …”
Section: Proofmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in most of the cases it is possible to consider only a finite set of contexts C Σ ⊆ C {s} Σ instead of the set C {s} Σ , inducing this way the formation of finite specifications SP s (cf. [1,12,19]). …”
Section: Proofmentioning
confidence: 99%
“…The study of methods for observational verification of properties can be found, for example, in works of M. Bidoit and R. Hennicker, of J. Goguen, G. Malcolm and G. Roşu, of A. Bouhoula, of R. Diaconescu, of K. Futatsugi, of P. Padawitz among others (cf. [1,15,13,12,21,7,9,20]). …”
Section: Introductionmentioning
confidence: 99%
“…CafeOBJ [26,27] is being built at the Japan Institute of Science and Technology under the direction of Prof. Kokichi Futatsugi; it extends OBJ3 with hidden algebra [55,80,68,67] for behavioral specification, and with rewriting logic [113,114] for applications programming. Maude [112,16] is being built at SRI International under the direction of Dr. Jose Meseguer; it extends OBJ with rewriting logic, and has been successfully used for metaprogramming, reflection, and algorithm implementation [17,18].…”
Section: A Brief History Of Objmentioning
confidence: 99%
“…The most relevant to the topic of this paper are the variations developed by Goguen et al (hidden logics [24,25]) and by Bidoit and Hennicker (observational logics [28,3]). These approaches formalize behavioral validity (correctness) as follows: hidden logic is a variant of the equational logic in which some part of the specification is visible and another is hidden.…”
Section: Introductionmentioning
confidence: 99%